Climate profiles and policy frameworks in agriculture and energy sectors in Benin and Burkina Faso - Ekpé, Sévérin; Sougué, Madou; Hackman, O Kwame; Gandji, Kisito; Ouedraogo, Ramata; Segnon, Alcade Christel; Salack, Seyni; Zougmore, Robert Bellarmin (2025)
Climate change is exacerbating vulnerabilities in Benin and Burkina Faso, where livelihoods and economic development depend heavily on agriculture and energy, two climate-sensitive sectors. Both countries are already experiencing rising temperatures, variable rainfall, and more frequent extreme weather events, which threaten food security and energy infrastructure development and efficiency. Both countries have ambitious climate commitments with well-aligned climate policy frameworks that are consistent with their national development goals and priorities, regional (AU and ECOWAS) agendas, and global climate policies such as the Paris Agreement. These frameworks prioritize sustainable land management and renewable energy toward low-carbon and climate-resilient development. Effective implementation of these frameworks is hindered by systemic barriers, mainly financial barriers: both sectors face critical funding shortfalls and heavy reliance on unpredictable external financing tied to donor priorities. Future climate projections indicate continued warming, increased droughts, and more intense rainfall events, leading to heightened risks for rural populations who depend on rain-fed agriculture and biomass energy. Bridging these gaps is essential to moving from ambition to measurable impact. Targeted GCF interventions could play a catalytic role by scaling up financing, strengthening institutional and technical capacities, and fostering regional coherence in line with ECOWAS and global climate priorities.